iPath3.0: interactive pathways explorer v3 - Darzi, Youssef; Letunić, Ivica; Bork, Peer; Yamada, Takuji (Nucleic acids research, 2018)
Abstract. iPath3.0 (http://pathways.embl.de) is a web-application for the visualization and analysis of cellular pathways. It is freely available and open to e